2014
DOI: 10.3389/fnagi.2014.00213
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Acetylcholine Receptor Density in Cognitively Intact Subjects at an Early Stage of Parkinson’s Disease

Abstract: We investigated in vivo brain nicotinic acetylcholine receptor (nAChR) distribution in cognitively intact subjects with Parkinson’s disease (PD) at an early stage of the disease. Fourteen patients and 13 healthy subjects were imaged with single photon emission computed tomography and the radiotracer 5-[123I]iodo-3-[2(S)-2-azetidinylmethoxy]pyridine ([123I]5IA). Patients were selected according to several criteria, including short duration of motor signs (<7 years) and normal scores at an extensive neuropsychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Results of animal model studies also indicated that increased striatal glutamatergic activity is implicated in the development and maintenance of LIDs 31, 32. Recent studies showed that nAChR agonists (e.g., nicotine) attenuate LIDs, especially when striatal dopamine transmission is relatively intact 10, 33. This effect is believed to occur through desensitization of nAChRs, with a consequent decline in nAChR‐mediated function,34 and release of glutamate from cortical and thalamic afferent 35, 36.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of animal model studies also indicated that increased striatal glutamatergic activity is implicated in the development and maintenance of LIDs 31, 32. Recent studies showed that nAChR agonists (e.g., nicotine) attenuate LIDs, especially when striatal dopamine transmission is relatively intact 10, 33. This effect is believed to occur through desensitization of nAChRs, with a consequent decline in nAChR‐mediated function,34 and release of glutamate from cortical and thalamic afferent 35, 36.…”
Section: Discussionmentioning
confidence: 99%
“…SPECT scans were performed 240 min after an intravenous single bolus injection of 187.3 ± 7.2 MBq of 123 I‐5‐IA 9, 10. These data were compared with a group of 12 healthy subjects (HC) age‐ (63.9 ± 11.7 years) and gender‐matched (5 males) 11, 12.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SPECT studies using [ 123 I]-5IA showed in early cognitively normal PD patients significantly higher nAChR density in the putamen, the insular cortex, and the supplementary motor area and lower in the caudate nucleus, the orbitofrontal cortex, and the middle temporal gyrus. Disease duration positively correlated with nAChR density in the putamen ipsilateral but not contralateral to the clinically most affected side (Isaias et al, 2014). Advanced PD patients without dementia showed a widespread nAChR decrease, ranging between 10% and 25%, in cortical and subcortical areas (Fujita et al, 2006;Lorenz et al, 2014;Oishi et al, 2007), and a significant correlation was found between cognitive dysfunction and cortical nAChR uptakes (Lorenz et al, 2014).…”
Section: Cholinergic Systemmentioning
confidence: 90%
“…Two selective SPECT radioligands, [ 123 I]-QNB and [ 123 I]-5IA, have been used to assess postsynaptic cholinergic system availability of M1 mAChR and α4β2 nAChR, respectively (Colloby et al, 2005;Fujita et al, 2006;Isaias et al, 2014;Lorenz et al, 2014;Oishi et al, 2007). SPECT studies using [ 123 I]-5IA showed in early cognitively normal PD patients significantly higher nAChR density in the putamen, the insular cortex, and the supplementary motor area and lower in the caudate nucleus, the orbitofrontal cortex, and the middle temporal gyrus.…”
Section: Cholinergic Systemmentioning
confidence: 99%